Evaluating the adoption of evidence-based practice using Rogers's diffusion of innovation theory: a model testing study - Mohammad Mehdi Mohammadi; Roghayeh Poursaberi; Mohammad Reza Salahshoor (Tabriz University of Medical Sciences, 2018)
Background: Despite the emergence and development of evidence-based practice (EBP) in recent years, its adoption continues to be limited. This study used Rogers's diffusion of innovation theory to identify the factors that advance EBP adoption, determine the process by which such adoption occurs, and develop an EBP adoption model.Methods: This descriptive correlational study with model testing design conducted in 2015.Data were collected from 482 individuals (322 nurses and 160 nursing students) applying a demographic information questionnaire, a standard scale for the perception EBP attributes, an EBP scale, and an individual innovation inventory. The relationships between variables we reexamined by path analysis.Results: The results showed that EBP adoption had a significant positive relationship with individual innovation (r = 0.578, P < 0.001), knowledge (r = 0.657, P < 0.001), attitude (r = 0.623,P < 0.001), and age (r = 0.357, P < 0.001). The findings of path analysis indicated that the goodness of fit indices such as goodness of fit index (GFI) = 0.999, comparative fit index (CFI)= 0.999, root mean square error of approximation (RMSEA) = 0.036 were in the ideal ranges.Knowledge (total effect=0.309, P < 0.001), attitude (total effect = 0.372, P = 0.002), and work experience (total effect=0.321, P = 0.003) had the highest coefficient in the model.Conclusion: The results suggested that EBP adoption was influenced by various factors, such as individual innovation, attitude, knowledge, and the perception of EBP attributes. Among these factors, attitude had the greatest effect on EBP adoption. The findings can serve as a guide for the identification of factors that effectively influence EBP adoption. They can also be used as bases for the design of training programs intended to enhance the adoption of EBP.